A handheld HIV detection platform using paper-based sample preparation and real-time isothermal amplification - George Adedokun; Gurjit Sidhu; Morteza Alipanah; Gary P. Wang; Z. Hugh Fan (Microsystems & Nanoengineering)
Abstract Early and accurate diagnosis of human immunodeficiency virus (HIV) infection is essential for timely initiation of antiretroviral therapy (ART) and prevention of new infections. However, conventional nucleic-acid-based tests for HIV detection require sophisticated laboratory equipment and trained personnel, which are often unavailable at the point-of-care (POC) or unaffordable in resource-limited settings. We report our development of a low-cost, integrated platform for POC testing of HIV. The platform integrates viral nucleic acid extraction on a paper substrate and reverse transcription loop-mediated isothermal amplification (RT-LAMP) in a portable, battery-powered heating device with real-time detection. The platform does not require laboratory infrastructure such as power outlets. The assay showed a detection limit of 30 copies/mL of HIV RNA in 140 μL human serum or 4 copies/reaction using 50 μL human serum, with no cross-reactivity with hepatitis C virus (HCV). We validated the platform using both plasma samples spiked with HIV and clinical samples from HIV-positive individuals, and compared it with standard laboratory assays based on polymerase chain reaction (PCR). These results demonstrate the feasibility of our platform for HIV testing at the POC.